Implante de queratinócitos autólogos em úlceras de membros inferiores de pacientes com seqüelas de hanseníase - Vilani-Moreno, Fátima Regina; Guimarães, Heloísa Cristina Passos; Bassoli, Sidinéia Raquel Bazalia; Oda, Roseli Marega; Mozer, Érika; Delanina, Wladimir Fiori Bonilha; Trindade, Maria Ângela Bianconcini; Lastória, Joel Carlos [UNESP]; Cleto, Norma Gondim (My University, 2013)
The occurrence of ulcers in leprosy is mainly due to the existence of numb areas that can easily undergo trauma and burns and thereafter become secondarily infected. This study aimed to treat ulcers in lower limbs of patients with leprosy sequelae through the implantation of autologous keratinocytes. The study consisted of fourteen patients (six with a single ulcer, four with more than one ulcer in the same limb and four with ulcers in both limbs) with a total of 31 ulcers. A fragment of healthy skin was collected and subjected to enzymatic digestion to obtain keratinocytes, which were then cultured for four weeks. The resulting keratinocytes were implanted in ulcers in combination with fibrin glue. Patients were followed for two months and the ulcers were monitored weekly during this time. Ulcers measuring ≤ 9.0 cm high x 5.0 cm wide (23 ulcers) decreased by 68.8% ± 27.1%, with nine of them showing complete healing. Larger ulcers decreased by 50.0% ± 31.9%, with two of these healing completely. Thus, implantation of autologous keratinocytes in combination with fibrin glue was effective in healing and/or reducing the ulcer size and should be considered as an additional ulcer treatment option in patients with leprosy sequelae.

Na hanseníase as úlceras podem surgir, principalmente, pelo fato de existirem áreas anestésicas, que com facilidade podem ser traumatizadas, queimadas e secundariamente infectadas. Este estudo teve por objetivo tratar as úlceras de membro inferior de pacientes com seqüelas de hanseníase por meio do implante de queratinócitos autólogos. Participaram 14 pacientes, sendo seis com uma única úlcera, quatro com mais de uma úlcera no mesmo membro inferior e quatro com úlceras nos dois membros, totalizando 31 úlceras. Um fragmento de pele sadia foi coletado e submetido à digestão enzimática para obtenção dos queratinócitos, que foram cultivados em meio específico, por quatro semanas. Os queratinócitos foram implantados nas úlceras em associação com cola de fibrina, as quais foram acompanhadas semanalmente, por dois meses. As úlceras cujas medidas eram ≤ a 9,0 cm de altura x 5,0 cm de largura (total de 23 úlceras) tiveram redução de tamanho em 68,8 ± 27,1%, sendo que nove delas apresentaram cicatrização total; àquelas com tamanho superior a esta medida diminuíram 50,0 ± 31,9%, sendo que duas cicatrizaram totalmente. Assim, o implante de queratinócitos autólogos em associação com cola de fibrina se mostrou eficaz na cicatrização e/ou redução do tamanho das úlceras e constitui mais uma opção de tratamento para úlceras de pacientes com seqüelas de hanseníase.
Implantation of autologous keratinocytes in lower limb ulcers of patients with leprosy sequelae
Keywords: Leprosy; Keratinocytes; Lower limb ulcers; Fibrin glue; Hanseníase; Queratinócitos; Úlceras; Cola de fibrina